2013
DOI: 10.1128/mcb.00869-12
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Mechanisms of N-Formyl-Methionyl-Leucyl-Phenylalanine-Induced Superoxide Generation and Degranulation in Mouse Neutrophils: Phospholipase D Is Dispensable

Abstract: Phospholipase D (PLD), which produces the lipid messenger phosphatidic acid (PA), has been implicated in superoxide generation and degranulation in neutrophils. The basis for this conclusion is the observation that primary alcohols, which interfere with PLD-catalyzed PA production, inhibit these neutrophil functions. However, off-target effects of primary alcohols cannot be totally excluded. Here, we generated PLD ؊/؊ mice in order to reevaluate the involvement of PLD in and investigate the molecular mechanism… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
42
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 56 publications
(45 citation statements)
references
References 75 publications
2
42
0
1
Order By: Relevance
“…However, the involvement of PLD in these events became uncertain when it was shown that a newly developed PLD-specific inhibitor (FIPI) did not affect many of the biological processes that are inhibited by 1-butanol (19,20). Moreover, a recent study has also shown that several ethanol (a two-carbon primary alcohol)-sensitive events were not observed when more reliable techniques, such as a genetic deletion of PLD, were employed (21). Consistent with the concerns raised by these studies, we found that, although FIPI could block agonist-induced changes in PLD activity, it did not prevent the mechanically induced increase in PA or mTOR signaling.…”
Section: Discussionmentioning
confidence: 99%
“…However, the involvement of PLD in these events became uncertain when it was shown that a newly developed PLD-specific inhibitor (FIPI) did not affect many of the biological processes that are inhibited by 1-butanol (19,20). Moreover, a recent study has also shown that several ethanol (a two-carbon primary alcohol)-sensitive events were not observed when more reliable techniques, such as a genetic deletion of PLD, were employed (21). Consistent with the concerns raised by these studies, we found that, although FIPI could block agonist-induced changes in PLD activity, it did not prevent the mechanically induced increase in PA or mTOR signaling.…”
Section: Discussionmentioning
confidence: 99%
“…DOCK5-deficient (D5 Ϫ/Ϫ ) mice, PLD1-deficient (PLD1 Ϫ/Ϫ ) mice, and PLD2-deficient (PLD2 Ϫ/Ϫ ) mice have been described elsewhere (22,31,32). Mice homozygous for DOCK1 alleles containing floxed exon 1 (DOCK1 flox/flox ) will be described elsewhere.…”
Section: Methodsmentioning
confidence: 99%
“…14,15 In recent years, however, PLD inhibition has become achievable using small molecule inhibitors. 16 An inhibitor screen identified 5-fluoro-2-indolyl des-chlorohalopemide (FIPI) as a potent and reversible inhibitor of both PLD isoforms, with a half-life of 5.5 hours in vivo and moderate bioavailability.…”
mentioning
confidence: 99%